2004
DOI: 10.1557/proc-811-d2.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structural Properties of Hf-Based Gate Stack on Transistor Performance

Abstract: Electron traps in ALD and MOCVD HfO2 and HfSiO high-k dielectrics were investigated using both conventional DC and pulse measurements. It was found that the traps in the gate stack could be associated with defects of different activation energies and capture cross-sections. This points to potentially different origins of the electrically active defects, which can be either intrinsic or process-related. Structural non-uniformity of the high-k film, associated with grain formation and phase separation, may lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 3 publications
4
17
0
Order By: Relevance
“…The hydrogen species will then diffuse away the interface at the elevated temperature and results in the threshold voltage shift [197]. Similar phenomenon is also observed in high-j gate dielectric [198][199][200] but the physical origins of the NBTI are much complicated. As mentioned earlier, high-j materials are often found to have higher bulk oxide trap and interface trap density.…”
Section: Hot Carrier Effect and Negative Bias Temperature Instabilitiesmentioning
confidence: 58%
See 1 more Smart Citation
“…The hydrogen species will then diffuse away the interface at the elevated temperature and results in the threshold voltage shift [197]. Similar phenomenon is also observed in high-j gate dielectric [198][199][200] but the physical origins of the NBTI are much complicated. As mentioned earlier, high-j materials are often found to have higher bulk oxide trap and interface trap density.…”
Section: Hot Carrier Effect and Negative Bias Temperature Instabilitiesmentioning
confidence: 58%
“…It was found that the oxide trap and interface trap recoveries are about 40% and 25% respectively for HfSiON film [200]. It was also found that the higher initial trap density would lead to larger threshold voltage shift during the stressing [198]. This is an indirect evident for this conjecture.…”
Section: Hot Carrier Effect and Negative Bias Temperature Instabilitiesmentioning
confidence: 76%
“…As the interface becomes thinner, the difference between the pulsed and DC mobility for a given gate stack becomes greater. The overall degradation in the pulsed (intrinsic) mobility as the interface layer becomes thinner can be attributed to poorer interfacial layer quality [102] and greater effects of soft optical phonons [64] and crystallinity [21,103].…”
Section: The Effect Of Ftc On Channel Mobilitymentioning
confidence: 99%
“…1. Some of these factors [3] will also introduce intrinsic parameter fluctuations in the corresponding MOSFETs, similar to the fluctuations introduced by random discrete dopants and oxide thickness variations.…”
Section: Introductionmentioning
confidence: 99%